2015
DOI: 10.1089/acm.2015.0067
|View full text |Cite
|
Sign up to set email alerts
|

Equine-Assisted Activities and Therapy for Treating Children with Attention-Deficit/Hyperactivity Disorder

Abstract: This is the first study demonstrating that EAA/T is effective for improving core ADHD symptoms. On the basis of these results, EAA/T could be a viable treatment strategy as a part of a multimodal therapy for children with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 42 publications
1
47
0
1
Order By: Relevance
“…A few studies have demonstrated that the interactive experience with the horses enhance the motivation to learn [ 35 ]. Moreover, an earlier study has been published that EAA in ADHD could modulate functional connectivity in the regions related to default mode network and behavioral inhibition system relating with ADHD symptom improvement [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A few studies have demonstrated that the interactive experience with the horses enhance the motivation to learn [ 35 ]. Moreover, an earlier study has been published that EAA in ADHD could modulate functional connectivity in the regions related to default mode network and behavioral inhibition system relating with ADHD symptom improvement [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The participants were assigned with trial ID numbers, created by a researcher not otherwise involved in the study. Prior to the 16-week study program, both groups participated in a pre-comprehensive assessment within 2 weeks, including intelligence, attention and psychological evaluation using Korean-Wechsler Intelligence Scale for Children-Fourth Edition (K-WISC-IV), Conner’s Continuous Performance Test (CPT), Korean ADHD Rating Scale (K-ARS) and Pediatric Quality of Life Inventory (PedsQl), which were used in previous studies to examine therapeutic effects on ADHD or CP children [ 9 , 23 ]. 2-weeks after the program was completed, the post-test assessment, including attention and psychological evaluation was performed.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations